Genome Editing in Medicine: Tools and Challenges - Petraitytė, Gunda; Preikšaitienė, Eglė; Mikštienė, Violeta (Acta medica Lituanica, 2021)
Studies which seek fundamental, thorough knowledge of biological processes, and continuous advancement in natural sciences and biotechnology enable the establishment of molecular strategies and tools to treat disorders caused by genetic mutations. Over the years biological therapy evolved from using stem cells and viral vectors to RNA therapy and testing different genome editing tools as promising gene therapy agents. These genome editing technologies (Zinc finger nucleases, TAL effector nucleases), specifically CRISPR-Cas system, revolutionized the field of genetic engineering and is widely applied to create cell and animal models for various hereditary, infectious human diseases and cancer, to analyze and understand the molecular and cellular base of pathogenesis, to find potential drug/treatment targets, to eliminate pathogenic DNA changes in various medical conditions and to create future “precise medication”. Although different concerning factors, such as precise system delivery to the target cells, efficacy and accuracy of editing process, different approaches of making the DNA changes as well as worrying bioethical issues remain, the importance of genome editing technologies in medicine is undeniable. The future of innovative genome editing approach and strategies to treat diseases is complicated but interesting and exciting at once for all related parties – researchers, clinicians, and patients.